The spatiotemporal dynamics of visual attention during real-world event perception - Ringer, Ryan (Kansas State University, 2018)
Everyday event perception requires us to perceive a nearly constant stream of dynamic information. Although we perceive these events as being continuous, there is ample evidence that we “chunk” our experiences into manageable bits (Zacks & Swallow, 2007). These chunks can occur at fine and coarse grains, with fine event segments being nested within coarse-grained segments. Individual differences in boundary detection are important predictors for subsequent memory encoding and retrieval and are relevant to both normative and pathological spectra of cognition. However, the nature of attention in relation to event structure is not yet well understood. Attention is the process which suppresses irrelevant information while facilitating the extraction of relevant information. Though attentional changes are known to occur around event boundaries, it is still not well understood when and where these changes occur. A newly developed method for measuring attention, the Gaze-Contingent Useful Field of View Task (GC-UFOV; Gaspar et al., 2016; Ringer, Throneburg, Johnson, Kramer, & Loschky, 2016; Ward et al., 2018) provides a means of measuring attention across the visual field (a) in simulated real-world environments and (b) independent of eccentricity-dependent visual constraints. To measure attention, participants performed the GC-UFOV task while watching pre-segmented videos of everyday activities (Eisenberg & Zacks, 2016; Sargent et al., 2013). Attention was probed from 4 seconds prior to 6 seconds after coarse, fine, and non-event boundaries. Afterward, participants’ memories for objects and event order were tested, followed by event segmentation. Attention was predicted to either become impaired (attentional impairment hypothesis), or it was predicted to be broadly distributed at event boundaries and narrowed at event middles (the ambient-to-focal shift hypothesis). The results showed marginal evidence for both attentional impairment and ambient-to-focal shift hypotheses, however model fitness was equal for both models. The results of this study were then used to develop a proposed program of research to further explore the nature of attention during event perception, as well as the ability of these two hypotheses to explain the relationship between attention and memory during real-world event perception.
Keywords: Attention; Event segmentation; Useful field of view; Event comprehension; Spatial attention; Eye-tracking